Attitude and Perceived Value on Intention to Revisit and Loyalty: A Theory of Planned Behavior Approach in Fast Food Retail - Ridha Septia Haruni Usman; Endy Gunanto Marsasi (Equity: Jurnal Ekonomi, 2025)
Fast food retail is a service that focuses on serving fast food. The development of this industry is relatively high and of course, this increases competition within it. The theory used as the grand theory in this research is the Theory of Planned Behavior. The Theory of Planned Behavior states that the factors influencing actual behavior are perceived behavioral control, attitude, and subjective norms.This study examines four factors influencing intention to revisit and customer loyalty: perceived value, subjective norm, attitude and quality. Researchers added perceived value as a novelty in this research. The object of this research is the fast food retail. The subjects in this research were fast food retail consumers ranging in age from 15 years to 50 years or generations Y and Z. Researchers used a quantitative approach in this study with a purposive sampling technique, which resulted in 200 samples. This research uses SEM analysis with AMOS Graphic software to manage data. The findings indicate that perceived value significantly affects attitude, while subjective norms do not significantly influence intention to revisit and loyalty. Moreover, attitude and quality play crucial roles in shaping customer loyalty and intention to revisit.